Effects of risk accountability on firm value : evidence from the appointment of chief risk officers or risk committees. - Ong, Fonzarelli. (2008)
This paper studies the relationship between risk accountability and firm value by investigating if the adoption of risk accountability mechanisms, evidenced by the appointment of a Chief Risk Officer or Risk Committee, would have an effect on firm value.